Significance of platelet indices in burns patient - Dr. Sofiya. C.; Dr. B. Pushpa (Tropical Journal of Pathology and Microbiology, 2017)
Introduction: Burns constitute an important health concern all over the world. The main aim of burns treatment is reducing morbidity and mortality. Platelet count was proved to be an important prognostic index in burns. The main aim of this study is to find the significance of other Platelet indices in burns patient. Methods: This study was conducted in a Tertiary care Hospital in Chennai for a sample size of 143 burns patients. Patients were divided into two groups based on the Total burn surface area (Group A with <30% Total Burns Surface Area and group B with >30% Total Burn Surface area). Normal persons with similar ages are taken as Control. Platelet indices were analysed for these patients on the day of admission and on the fourth day of admission using Sysmex 5-part analyser. BAUX score was also calculated for the Burns patient. The results were compared between platelet indices, clinical parameters and Baux score among different groups. Results: The results of platelet indices between group A, group B and control group were compared. In group A, no significant change in platelet indices was observed. But in group B, the mean value of Platelet count decreases from 217 on the day admission to 164 on the fourth day of admission and the Mean Platelet Volume increases from 9.88 on the day of admission to 10.54 on the fourth day of admission. Mean Platelet Volume also correlates linearly with BAUX score. Conclusion: BAUX score is a prognostic scoring system in which higher value indicates poorer prognosis. MPV correlates linearly with BAUX score which indicates raising MPV act as poor prognostic factor. Platelet indices which can be analyzed with simple automated analyser can act as important prognostic factor in burns patient which helps in deciding appropriate treatment at appropriate time.